Integrating Direct Teaching and Local Cultural Values to Improve Student Engagement and Learning Outcomes in Islamic Religious Education for Fifth Grade Students - Klis Dianti; Luthfiyah Luthfiyah; Syarifuddin Syarifuddin (STAI Hubbulwathan Duri, 2025)
This study investigates the effectiveness of the Direct Instruction model integrated with the local cultural values of Maja Labo Dahu in enhancing student engagement and learning outcomes in Islamic Religious Education among fifth-grade students at INPRES Tololara State Elementary School. The integration of cultural elements aimed to make learning more relevant and character-building for students. A classroom action research (CAR) design was employed, conducted over two cycles. Each cycle involved stages of planning, implementation, observation, and reflection. The participants were 15 fifth-grade students. Data were collected through structured observations of student learning activities and evaluations of student learning outcomes. The findings revealed notable improvements in both student engagement and academic achievement. Student learning activity increased from 61.67% in the first cycle to 85% in the second, while classical learning completeness rose from 60% to 86.67%. These gains were attributed to clearer instructional guidelines, the integration of culturally familiar content, and the use of demonstration and practice-based teaching techniques. Reflective analysis from the first cycle allowed for refinement of teaching strategies in the second cycle, leading to enhanced student motivation, interaction, and comprehension. Beyond academic improvements, the integration of Maja Labo Dahu supported the development of character values aligned with Islamic teachings, such as integrity, respect, and cooperation. In conclusion, combining the Direct Instruction model with local cultural values proved effective in improving both cognitive and character outcomes, offering a viable approach to enhancing the quality of elementary education.